Dalang Anak dalam Pertunjukan Wayang - Junaidi Junaidi (Universitas Gadjah Mada, 2014)
Puppeteer puppet show presenter child as interesting to study, because adultsusually do, so there is a discrepancy between the condition of the child and puppet show format. Child Puppeteer appears in different areas, both in Java and the surrounding territory. Motivation theory is used to solve the presence of children in the puppet show, while the methods of qualitative research, based on fi les from the literature review and field observations. The results can be found that the child puppeteer motivation is internal and external, as an educative motive, preservation, and development of the art of puppetry to the next generation.